Planejamento de transporte cicloviário urbano: organização da circulação - Teramoto, Telmo Terumi (2007)
The spatial organization of Brazilian cities and the organization of their transportation systems have been causing an uneven accessibility distribution among other issues. This unbalance is marked by the fact that people who use private motorized modes of transportation are the ones that have been benefiting the most while the ones that use non motorized modes have been experiencing the worst conditions. The knowledge about the motorized transportation is much more developed than the knowledge regarding cycling as a mode of transportation. As long as this kind of unbalance remains there will not be equity in the society areas related to transportation. The purpose of this research is to provide general data and the fundamentals to permit the comprehension of the urban cycling transportation characteristics and the ways of organizing the cycling space as well. By evaluating different ways of organizing this space this dissertation presents the ones that had the best results or the ones that have the best potential to favourable results and that are also generic enough to be adequate to a great number of Brazilian localities. Within the chosen objectives the discussions and propositions presented in this dissertation are focused on introducing the bicyclists inside the road system so it would be possible to them to go everywhere in the cities under adequate conditions. Therefore the search was for discussions and propositions that took the bicyclists needs into consideration avoiding the ones that could exclude the bicyclists. This dissertation is focused on ways of organizing the cycling space that are suitable to new urbanization projects but specially on the ones that can fit to the areas with established road systems. This research allowed the verification that urban cycling transportation can really occur in a more harmonious way with the others modes of transportation. The presented and evaluated propositions indicate that cycling transportation is not incompatible with the motorized transportation